Endophytic bacteria of patchouli (Pogostemon cablin cv. Tapaktuan) as biocontrol agents against major soil-borne pathogens - SUHARTONO SUHARTONO; MILDA HUSNAH; ZUMAIDAR ZUMAIDAR; AMALIA AMALIA; ADELIA SALSABILA; ALFI MULIYANI; ARRAYYAN NAJLA ACHZA (Society for Indonesian Biodiversity, 2026)
Abstract. Suhartono S, Husnah M, Zumaidar Z, Amalia A, Salsabila A, Muliyani A, Achza AN. 2026. Endophytic bacteria of patchouli (Pogostemon cablin cv. Tapaktuan) as biocontrol agents against major soil-borne pathogens. Biodiversitas 27 (5): d270527. https://doi.org/10.13057/biodiv/d270527. Endophytic bacteria are increasingly recognized as valuable sources of biocontrol agents against soil-borne phytopathogens. The aim of this study was to evaluate the antifungal activity of 23 endophytic bacterial isolates obtained from patchouli (Pogostemon cablin cv. Tapaktuan) against Sclerotium rolfsii, Fusarium oxysporum, and Phytophthora capsici using a dual-culture assay. Antagonistic activity varied markedly among isolates, with inhibition of radial fungal growth ranging from 5.8±0.88% to 73.0±0.49%. Among all the tested isolates, DT-7 consistently exhibited the strongest antifungal activity, suppressing P. capsici, S. rolfsii and F. oxysporum, by 73.0±0.49%, 70.1±1.97% and 66.8±4.89%, respectively, resulting in an overall mean inhibition of 69.9±3.10%. The other two effective isolates included DT-4 and AT-7 (overall mean inhibition: 62.8±6.61% and 61.0±0.40%, respectively). Analysis of organ-associated patterns revealed that inhibition of S. rolfsii was generally higher among root-derived endophytes, whereas F. oxysporum and P. capsici were more effectively suppressed by leaf-derived endophytes. Statistically significant differences among plant organs were detected only for F. oxysporum, with root- and leaf-associated isolates showing higher inhibition than stem-associated isolates (F (2, 20) = 3.756; p = 0.041). Molecular identification based on 16S rRNA gene sequencing revealed that isolate DT-7 belonged to the genus Stutzerimonas, closely related to the Stutzerimonas stutzeri group, whereas AT-7 and DT-4 clustered within the Enterobacter genus. The consistent and broad-spectrum antifungal activity of DT-7 suggested its potential as a promising biocontrol candidate as a biological resource for sustainable disease management. In addition, the observed organ-specific inhibition patterns underscored the ecologically structured endophyte-pathogen interactions within patchouli tissues, providing a basis for further mechanistic and greenhouse studies. This study represents an in vitro screening with limited replication (n = 2 plates per treatment), providing a preliminary basis for subsequent greenhouse and field validation.